2020
DOI: 10.3389/fpsyg.2020.00239
|View full text |Cite
|
Sign up to set email alerts
|

Young Children’s Indiscriminate Helping Behavior Toward a Humanoid Robot

Abstract: Young children help others in a range of situations, relatively indiscriminate of the characteristics of those they help. Recent results have suggested that young children's helping behavior extends even to humanoid robots. However, it has been unclear how characteristics of robots would influence children's helping behavior. Considering previous findings suggesting that certain robot features influence adults' perception of and their behavior toward robots, the question arises of whether young children's beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 99 publications
1
5
0
Order By: Relevance
“…These exciting results suggest that IVR can be beneficial for assisting memory encoding and offer insight into how children's memory can be enhanced by this technology, not only as a potential memory aid but also as a possible means to help children learn. Moreover, our finding that children generally had positive experiences with IVR in conjunction with recent developmental VR studies of child perception (e.g., (Negen et al, 2018;Valori et al, 2020)) suggests that this technology can join others such as touchscreens and robots (e.g., (Martin et al, 2019(Martin et al, , 2020) in the growing technological pantheon of tools to probe important aspects of children's developing minds.…”
Section: Discussionsupporting
confidence: 60%
“…These exciting results suggest that IVR can be beneficial for assisting memory encoding and offer insight into how children's memory can be enhanced by this technology, not only as a potential memory aid but also as a possible means to help children learn. Moreover, our finding that children generally had positive experiences with IVR in conjunction with recent developmental VR studies of child perception (e.g., (Negen et al, 2018;Valori et al, 2020)) suggests that this technology can join others such as touchscreens and robots (e.g., (Martin et al, 2019(Martin et al, , 2020) in the growing technological pantheon of tools to probe important aspects of children's developing minds.…”
Section: Discussionsupporting
confidence: 60%
“…Our results provide new evidence that children attribute such EAP to social robots and assume that social robots can evaluate the behavior of others. Although previous research has shown that children anthropomorphize robots (e.g., Chernyak & Gary, 2016), learn from them (Kanero et al, 2018; Tanaka & Matsuzoe, 2012), imitate them to some extent (Sommer et al, 2020, 2021), help them (Martin et al, 2020), respond to questions from them (Okanda et al, 2013), are influenced by them in their decision‐making (Vollmer et al, 2018), and share their own costly resources with robots (Nijssen et al, 2021), this is the first evidence of children actually managing their reputations from robots.…”
Section: Discussionmentioning
confidence: 99%
“…TD adults are prone to anthropomorphism; i.e., they tend to attribute human characteristics to non-human entities, such as robots [114,115]. TD children are also affected by this phenomenon as they attribute desires and physiological states to robots [116], interpret their movements as goal-directed [117], and seek to help them [118]. Insofar as autistic and neurotypical children categorize robots in similar ways, we might wonder whether they also exhibit the same level of anthropomorphism.…”
Section: Difference In Robot Anthropomorphism Between Typical Develop...mentioning
confidence: 99%